The unexpected bilateral Tuberculous empyema: a case report in a child - Ismail, Intan Hakimah; Mohd Fakharuddin, Mohd. Feizel Alsiddiq; Othman, Norlijah; Mohd Noh, Lokman; Wan-Azfa, Farahiah WZ (Poracom Academic Publishers, 2008)
Tuberculous pleurisy is characterised by unilateral exudates with predilection on the right side, whereas bilateral involvement is rarely encountered. A positive history of contact with tuberculous case and a negative Bacillus Calmette-Guerin (BCG) vaccination scar are usually seen. Here we illustrate a case of bilateral tuberculous lung empyema in a previously healthy child with a presence of BCG scar and an initial non-existence contact history with tuberculosis patient.